β-Carbon activation of saturated carboxylic esters through N-heterocyclic carbene organocatalysis - Xu, Jianfeng (2013)
The activation of the α-carbons of carboxylic esters and related carbonyl compounds to generate enolate equivalents as nucleophiles is one of the most powerful strategies in organic synthesis. We reasoned that the horizons of chemical synthesis could be greatly expanded if the typically inert β-carbons of saturated esters could be used as nucleophiles. However, despite the rather significant fundamental and practical values, direct use of the β-carbons of saturated carbonyl compounds as nucleophiles remains elusive. Here we report the catalytic activation of simple saturated ester β-carbons as nucleophiles (β-carbon activation) using N-heterocyclic carbene organocatalysts. The catalytically generated nucleophilic β-carbons undergo enantioselective reactions with electrophiles such as enones and imines. Given the proven rich chemistry of ester α-carbons, we expect this catalytic activation mode for saturated ester β-carbons to open a valuable new arena for new and useful reactions and synthetic strategies.